Teaching Quality Indicators Pilot Project : Final Report : [University of Western Australia]. - Flowers, Jacqueline (Australian Learning and Teaching Council (ALTC), 2009)
The Australian Learning and Teaching Council (ALTC) project 'Rewarding and recognising quality teaching in higher education through systematic implementation of indicators and metrics on teaching and teacher effectiveness' (short title The Teaching Quality Indicators or TQI Project) had as its central principle the concept that teaching quality is contextual and will mean different things depending on the institutional environment in which it is being discussed and examined. The project is also based on the assumption that teaching quality is multi-dimensional and that the indicators and outcomes of teaching quality that are prioritised within institutions will vary according to institutional priorities and context. This is the final report on how the project was conducted at University of Western Australia.